Directional energy deposition laminated structure Cu-Fe additive part based on wire and preparation method and application of directional energy deposition laminated structure Cu-Fe additive part
Cu and Fe wires are alternately deposited through wire directional energy deposition technology to form a laminated structure Cu-Fe additive parts, solving the defect problems in the cooling process of Cu-Fe alloys, and achieving the coordinated improvement of material performance and high efficiency and low cost characteristics of the process.
Patent Information
- Application Number
- CN202510009473.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-03
AI Technical Summary
During the cooling process, Cu-Fe alloy is prone to defects such as segregation, shrinkage and shrinkage holes, which affects its mechanical properties and conductivity, and hinders its further development as a high-performance copper alloy.
Using wire directional energy deposition technology, Cu-Fe additive parts are formed by alternately deposition of Cu wire and Fe wire, welding current and voltage are regulated, and the Cu/Fe phase interface width and interface bond strength are controlled to form a laminated structure Cu-Fe additive parts.
It effectively improves the mechanical properties and conductivity of Cu-Fe alloys, reduces the risk of defects, improves the overall performance of the material, and has high stacking rate, low cost and dimensional flexibility in the process.
Smart Images

Figure BDA0005227938050000061 
Figure HDA0005227938070000011 
Figure HDA0005227938070000012
Abstract
Description
Technical Field
[0001] The invention relates to a wire-based directed energy deposition laminated structure Cu-Fe additive component and a preparation method and application thereof, belonging to the technical field of high-strength and high-conductivity copper alloys. Background Art
[0002] High-performance copper alloys are key basic materials in the fields of new-generation information technology, advanced rail transit equipment, and other high-tech fields that my country focuses on developing. They have a series of excellent properties such as high electrical conductivity, high thermal conductivity, high strength, high corrosion resistance, plating ability, and easy processing. The development of high-performance electromechanical equipment requires alloy materials with higher strength and better electrical conductivity. Cu-Fe alloys are strategic basic materials that my country urgently needs to develop a new generation of low-cost, high-performance Cu alloys.
[0003] Mechanical properties and electrical conductivity are the most striking and important characteristics of conductive metal materials used in electrical engineering. However, there is an intrinsic contradiction between the two in copper and its alloys. Due to its physical properties, strengthening one is often accompanied by sacrificing the performance of the other. The microstructural regulation of Cu-Fe alloys to achieve a balance between high strength and high electrical conductivity of the material is in line with the current rapid economic development and the growing demand for energy, as well as the core demand of enterprises to reduce costs.
[0004] Cu-Fe alloy has a liquid phase separation zone during the cooling process, and is prone to defects such as segregation, shrinkage and shrinkage during cooling and solidification. This seriously affects the mechanical properties and electrical conductivity of Cu-Fe alloy, and hinders the further development of Cu-Fe alloy as a high-performance copper alloy.
[0005] Since the directed energy deposition technology has the characteristics of adjustable melting temperature and short molding time, it avoids the uneven melting and mutual diffusion of Cu and Fe during high-temperature melting and casting. It can achieve the regulation of the Cu / Fe phase interface, so that the mechanical properties and electrical conductivity of the additive parts are synergistically improved.
[0006] At present, there are no reports on the use of wire and directed energy deposition technology to prepare Cu-Fe alloy additive parts with laminated structures, nor have the Cu / Fe phase interface control means and composite mechanism, as well as the strengthening-conductivity mechanism of Cu-Fe heterogeneous structures, been elucidated. Therefore, the study of the use of wire and directed energy deposition technology to prepare Cu-Fe additive parts with laminated structures and their phase interface control can provide a theoretical basis for the preparation of high-strength and high-conductivity Cu-Fe alloy materials and broaden their application areas. Summary of the invention
[0007] Purpose of the invention: In view of the shortcomings of the prior art, the first purpose of the present invention is to provide a Cu-Fe additive component with a directed energy deposition laminated structure based on wire, and the second purpose of the present invention is to provide a method for preparing the Cu-Fe additive component with a directed energy deposition laminated structure based on wire. The third purpose of the present invention is to provide the application of the Cu-Fe additive component with a directed energy deposition laminated structure based on wire in high-performance electromechanical equipment.
[0008] Technical solution: The present invention discloses a Cu-Fe additive part with a laminated structure based on wire-based directed energy deposition, which is a Cu-Fe additive part with a laminated structure in which Cu and Fe are alternately formed by wire-based directed energy deposition technology.
[0009] Further, the wire directed energy deposition technology is a gas metal arc welding technology, a non-metallic metal arc welding technology, a plasma arc welding technology and / or a cold metal transfer technology (CMT).
[0010] Furthermore, the heat source of the wire directed energy deposition technology is a laser, an electron beam, a plasma arc and / or an electric arc.
[0011] The method for preparing a Cu-Fe additive component with a directed energy deposition laminate structure based on wire material according to the present invention comprises the following steps:
[0012] The Cu welding wire and the Fe welding wire are alternately fed into the molten pool for deposition using wire directed energy deposition technology. By adjusting the welding current and voltage and the heat input of the current deposition layer, the width of the Cu / Fe phase interface and the interface bonding strength can be effectively controlled.
[0013] Furthermore, the Cu welding wire and the Fe welding wire are doped with alloy elements, and the alloy elements are one or more of Si, V, Mn, Cr, Ni, Al, and rare earth elements.
[0014] Furthermore, the rare earth element is Y, Gd and / or Nd, etc.
[0015] Furthermore, during the Cu wire deposition process, the welding gun oscillates in a triangular wave along the traveling direction, and the Cu layer structures of different widths and thicknesses can be obtained by adjusting the oscillation amplitude and oscillation step length.
[0016] Furthermore, the alternating stacked structure of Cu and Fe is more than one layer.
[0017] Furthermore, the wire feeding speed of the Cu welding wire is 10-15 m / min, and the wire feeding speed of the Fe welding wire is 8-12 m / min.
[0018] Furthermore, the Cu wire welding current is 137-243A, and the welding voltage is 11.6-23.5V.
[0019] Furthermore, the Fe wire welding current is 120-226A, and the welding voltage is 11.2-22.3V.
[0020] The invention discloses an application of the wire-based directed energy deposition laminated structure Cu-Fe additive parts in high-performance electromechanical equipment.
[0021] The present invention regulates the welding current and voltage, regulates the heat input of the current deposited layer, thereby regulating the organizational morphology of the Fe phase in the Cu deposited layer, the interface bonding between the forming surface and the current deposited layer, and the element transition at the interface, forming a spherical Fe phase and a dendritic Fe phase, and the interface layer is well bonded without obvious defects. The prepared laminated structure Cu-Fe additive parts include laminated structure additive parts with only one Cu deposited layer and Fe deposited layer and laminated structure additive parts with multiple Cu deposited layers and Fe deposited layers.
[0022] According to the preset ratio of Cu and Fe in a Cu-Fe additive part and the required Cu-Fe interface layer effect, the wire feeding speeds of the Cu welding wire and the Fe welding wire are respectively set, the Cu welding wire is used to deposit a first layer on a substrate, and when the Cu deposited layer is cooled to 100°C, the welding wire is replaced with the Fe welding wire and the same arc starting point and arc ending point are maintained, and the welding gun is raised by 3mm to continue depositing the second layer; then the deposition process is continuously repeated until the required size of the additive part is reached; under the action of heat input and arc stirring, the forming surface is affected by the next deposition layer and partially remelted, the Fe phase in the Cu deposition layer mainly exists in the form of micron-level spherical and dendritic second phases, the Cu deposition layer and the Fe deposition layer are well bonded at the interface, and a laminated structure Cu-Fe additive part is obtained.
[0023] The present invention deposits Cu welding wire and Fe welding wire alternately on a substrate to obtain a laminated structure Cu-Fe additive part; the proportion of Cu and Fe elements in the additive part is regulated by controlling the wire feeding speed, and the interface fusion state of the Cu and Fe deposition layers and the element transition at the interface are regulated by controlling the welding current and voltage; the prepared Cu-Fe alloy additive part has higher strength, hardness, electrical conductivity and work hardening ability than the Cu-Fe total ingot prepared by the traditional melting and casting method; the preparation of Cu-Fe additive parts by directed energy deposition can solve the problem of performance degradation caused by material metallurgical incompatibility in other preparation processes; and the preparation of Cu-Fe additive parts by wire-based directed energy deposition has the characteristics of relatively high stacking rate, low cost, small size restriction and the like compared with other additive processes, and has great potential in the construction of large structural parts with complex structures.
[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0025] (1) In the wire-based directed energy deposition laminated structure Cu-Fe additive parts of the present invention, spherical Fe phases and dendritic Fe phases appear in the Cu deposition layer, and the interface between the Cu deposition layer and the Fe deposition layer is well bonded without obvious defects.
[0026] (2) The directed energy deposition based on the wire of the present invention has the characteristics of adjustable melting temperature and short molding time, which avoids the uneven melting and mutual diffusion of Cu and Fe during high-temperature melting and casting. It effectively improves the mechanical properties of the material and reduces the risk of defects such as cracks and pores in the components, thereby meeting its safe service requirements. The realization of low heat input and precise fuse quantity control effectively regulates the melting of Cu and Fe and the interface bonding between the Cu deposition layer and the Fe deposition layer.
[0027] (3) The hardness of the Cu-Fe additive parts obtained by the present invention reaches 190HV, the tensile strength in the building direction is 382MPa, the tensile strength in the scanning direction is 591MPa, and the electrical conductivity is 68%IACS; the tensile strength of the Cu-Fe additive parts prepared by the directed energy deposition process in the present invention in the building direction and the scanning direction are better than those of the traditional melt casting method, and the hardness and electrical conductivity are increased by 58% and 30.7% respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a diagram of the directed energy deposition experimental platform;
[0029] Figure 2 Schematic diagram of the preparation process of Cu-Fe alloy with laminated structure by directed energy deposition based on wire;
[0030] Figure 3 This is a diagram of a Cu-Fe alloy additive part with a laminated structure based on wire-based directed energy deposition;
[0031] Figure 4 This is a cross-sectional macroscopic morphology of a Cu-Fe alloy additive part with a laminated structure based on wire-based directed energy deposition;
[0032] Figure 5 This is the metallographic structure diagram at the interface of the laminated structure Cu-Fe alloy additive component in Example 1;
[0033] Figure 6 This is the metallographic structure diagram at the interface of the laminated structure Cu-Fe alloy additive component in Example 2;
[0034] Figure 7 This is the metallographic structure diagram at the interface of the laminated structure Cu-Fe alloy additive component in Example 3;
[0035] Figure 8 This is the metallographic structure diagram at the interface of the laminated structure Cu-Fe alloy additive component in Example 4;
[0036] Fig. 9 This is the macroscopic morphology of the laminated structure Cu-Fe alloy additive component in Example 5. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0038] The Cu-Fe alloy additive parts were prepared by using a single-wire WAAM platform robot. The main equipment for the experiment was the FRONIUS digital pulse MIG / MAG welder-TPS4000 and an ABB industrial robot (such as Figure 1 shown).
[0039] The following experiment uses a single-wire WAAM platform to alternately deposit commercial Cu welding wire SCu6180 with a diameter of 1 mm and Fe welding wire MG50-6 with a diameter of 0.8 mm to obtain a laminated structure Cu-Fe additive part. The CMT cold metal transfer welding technology is used to complete the additive operation. The materials involved in the following experiments can all be obtained from commercial channels.
[0040] Example 1
[0041] like Figure 2 As shown in the figure, first, Cu welding wire SCu6180 is used to add material on the 45 steel substrate, the wire feeding speed is 10m / min, the welding current is 137A, and the welding voltage is 11.6V. After the temperature of the current deposited layer (thickness is about 3mm) is cooled to 100℃, the Fe welding wire MG50-6 is replaced and deposited on the Cu forming surface, while keeping the same arc starting point and arc ending point, and the welding gun is raised by 3mm, the Fe welding wire feeding speed is 8m / min, the welding current is 120A, and the welding voltage is 11.2V. A single-layer Cu-Fe additive part is obtained, as shown in FIG. Figure 3 Then, Cu and Fe are deposited alternately with the same parameters until the required number of layers of the preset additive part is reached. Finally, the Fe deposition layer accounts for 20.02% of the Cu-Fe additive part. In this embodiment, 17 layers are deposited in total. Figure 3-4 shown.
[0042] The metallographic analysis of the multilayer Cu-Fe additive component prepared in this embodiment is as follows: Figure 5 shown. Figure 5 It shows that the Fe phase in the Cu deposited layer of the laminated Cu-Fe additive part mainly exists in the form of spherical and dendritic second phases, and there are slight protrusions at the interface between the Cu and Fe deposited layers. Performance tests show that the laminated Cu-Fe additive part has a hardness of 172HV, a tensile strength of 363MPa in the build direction, a tensile strength of 556MPa in the scan direction, and an electrical conductivity of 61%IACS.
[0043] Example 2
[0044] The preparation process is the same as that in Example 1, except that the wire feeding speed, welding current and welding voltage are controlled differently. First, Cu welding wire SCu6180 is used to add material on a 45 steel substrate, with a wire feeding speed of 12m / min, a welding current of 196A, and a welding voltage of 22.1V. After the temperature of the current deposited layer (thickness of about 3mm) is cooled to 100°C, Fe welding wire MG50-6 is replaced and deposited on the Cu forming surface, while maintaining the same arc starting point and arc ending point and raising the welding gun by 3mm, the wire feeding speed of Fe welding wire is 10m / min, the welding current is 176A, and the welding voltage is 16.5V. Then continue to alternately deposit with the same parameters to the required number of layers of the preset additive part, and the Fe deposition layer accounts for 23.46% in the final Cu-Fe additive part.
[0045] The metallographic analysis of the multilayer Cu-Fe additive component prepared in this embodiment is as follows: Figure 6 shown. Figure 6 It shows that in this embodiment, the Fe phase in the Cu deposited layer of the laminated Cu-Fe additive part mainly exists in the form of small spherical and dendritic second phases, and the interface between the Cu and Fe deposited layers is straight, well bonded and has no obvious defects. Performance tests show that the laminated Cu-Fe additive part has a hardness of 190HV, a tensile strength of 382MPa in the build direction, a tensile strength of 591MPa in the scan direction, and an electrical conductivity of 68%IACS.
[0046] Example 3
[0047] The preparation process is the same as that in Example 1, except that the wire feeding speed, welding current and welding voltage are controlled differently. First, Cu welding wire SCu6180 is used to add material on a 45 steel substrate, with a wire feeding speed of 15m / min, a welding current of 243A and a welding voltage of 23.5V. After the temperature of the current deposited layer (thickness of about 3mm) is cooled to 100°C, Fe welding wire MG50-6 is replaced and deposited on the Cu forming surface, while maintaining the same arc starting point and arc ending point and raising the welding gun by 3mm, the wire feeding speed of Fe welding wire is 12m / min, the welding current is 226A, and the welding voltage is 22.3V. Then continue to alternately deposit with the same parameters to the required number of layers of the preset additive part, and the Fe deposition layer accounts for 25.76% in the final Cu-Fe additive part.
[0048] The metallographic analysis of the multilayer Cu-Fe additive component prepared in this embodiment is as follows: Figure 7 shown. Figure 7It is shown that in this embodiment, the Fe phase in the Cu deposited layer in the laminated Cu-Fe additive part mainly exists in the form of a spherical second phase and a small amount of dendritic second phase. Due to the large heat input and thermal cycling, the Fe phase in the Cu deposited layer is unevenly distributed. At the same time, defects appear at the interface of the Cu and Fe deposited layers, and microcracks are generated in the Fe deposited layer. Performance tests on it show that the hardness of the laminated Cu-Fe additive part is 149HV, the tensile strength in the build direction is 345MPa, the tensile strength in the scanning direction is 536MPa, and the electrical conductivity is 56%IACS.
[0049] Example 4
[0050] The preparation process is the same as that in Example 1, except that the wire feeding speed, welding current and welding voltage are controlled differently. First, S211 silicon bronze wire is used for deposition on a 45 steel substrate. The S211 silicon bronze wire contains 3% silicon and 1% manganese. The wire feeding speed is 15m / min, the welding current is 243A, and the welding voltage is 23.5V. After the temperature of the current deposited layer (thickness of about 3mm) is cooled to 100°C, the Fe welding wire MG50-6 is replaced and deposited on the Cu forming surface, while maintaining the same arc starting point and arc ending point and raising the welding gun by 3mm, the wire feeding speed of the Fe welding wire is 12m / min, the welding current is 226A, and the welding voltage is 22.3V. Then continue to alternately deposit with the same parameters to the required number of layers of the preset additive part, and the Fe deposition layer accounts for 25.31% of the final Cu-Fe additive part.
[0051] The metallographic analysis of the multilayer Cu-Fe additive component prepared in this embodiment is as follows: Figure 8 shown. Figure 8 It shows that in this embodiment, a large amount of dendritic Fe phase and a small amount of spherical Fe second phase appear in the Cu deposition layer of the laminated structure Cu-Fe additive part. At the same time, a large protruding area appears at the interface of the Cu and Fe deposition layers. Performance testing shows that the laminated Cu-Fe additive part has a hardness of 162HV, a tensile strength of 377MPa in the build direction, a tensile strength of 547MPa in the scanning direction, and a conductivity of 59%IACS.
[0052] Example 5
[0053] The preparation process is the same as that in Example 1, except that the wire feeding speed, welding current and welding voltage are controlled differently. First, the Cu welding wire SCu6180 is used to add material on the substrate. The wire feeding speed is 7m / min, the welding current is 112A, and the welding voltage is 10.3V. After the temperature of the current deposited layer (thickness is about 3mm) is cooled to 100°C, the Fe welding wire MG50-6 is replaced and deposited on the Cu forming surface. At the same time, the same arc starting point and arc ending point are maintained and the welding gun is raised by 3mm. The wire feeding speed of the Fe welding wire is 6m / min, the welding current is 103A, and the welding voltage is 10.8V. Then continue to deposit alternately with the same parameters to the required number of layers of the preset additive parts. In this embodiment, due to the low welding current and voltage parameters and insufficient welding heat input, the Cu-Fe alloy additive parts are poorly formed and cannot meet the required additive parts use requirements. Fig. 9 shown.
[0054] Comparative Example 1
[0055] The conventional melting and casting process uses pure Cu (99.95wt%) and Fe (99.99wt%) in the required proportion of Cu80Fe20 to produce Cu-Fe alloy workpieces. Cu metal ingots and Fe metal ingots with a ratio of 80% Cu and 20% Fe are placed in an arc melting furnace for pre-alloying, and the furnace chamber is evacuated and purged with high-purity argon gas many times. To ensure the uniformity of the alloy, the sample is repeatedly melted 3 times. The alloy is then re-melted by induction melting in a ceramic crucible and poured into the prepared mold. The final Cu-Fe alloy workpiece has a hardness of 120HV, a tensile strength of 340MPa, and a conductivity of 52%IACS.
[0056] The process parameters and performance results of Examples 1-5 and Comparative Example 1 are shown in Table 1.
[0057] Table 1 Arc additive manufacturing parameters and performance
[0058]
[0059] It can be seen from Table 1 that in the embodiment of the present invention, the best performance Cu-Fe additive part has a hardness of 190HV, a tensile strength of 382MPa in the building direction, a tensile strength of 591MPa in the scanning direction, and an electrical conductivity of 68%IACS; the Cu-Fe additive part prepared by the directed energy deposition process of the present invention has better tensile strength in the building direction and the scanning direction than the traditional melt casting method, and the hardness and electrical conductivity are increased by 58% and 30.7% respectively.
[0060] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A directed energy deposition laminated structure Cu-Fe additive part based on wire, characterized in that: A Cu-Fe additive part with a stacked structure of alternating Cu and Fe is formed by wire directed energy deposition technology.
2. The wire-based directed energy deposition laminated structure Cu-Fe additive component according to claim 1, characterized in that: The wire directed energy deposition technology is a gas metal arc welding technology, a non-metal metal arc welding technology, a plasma arc welding technology and / or a cold metal transfer technology.
3. The wire-based directed energy deposition laminated structure Cu-Fe additive component according to claim 1, characterized in that: The heat source for wire directed energy deposition technology is laser, electron beam, plasma arc and / or electric arc.
4. The method for preparing a Cu-Fe additive component with a directed energy deposition laminate structure based on wire according to any one of claims 1 to 3, characterized in that: The following steps are involved: The Cu welding wire and the Fe welding wire are alternately fed into the molten pool for deposition using wire directed energy deposition technology. By adjusting the welding current and voltage and the heat input of the current deposition layer, the width of the Cu / Fe phase interface and the interface bonding strength can be effectively controlled.
5. The preparation method according to claim 4, characterized in that: The Cu welding wire and the Fe welding wire are doped with alloy elements, and the alloy elements are one or more of Si, V, Mn, Cr, Ni, Al, and rare earth elements.
6. The preparation method according to claim 4, characterized in that: During the Cu wire deposition process, the welding gun oscillates in a triangular wave along the traveling direction. By adjusting the oscillation amplitude and oscillation step length, the Cu layer structure with different width and thickness can be obtained.
7. The preparation method according to claim 4, characterized in that: The stacked structure of Cu and Fe alternately has more than one layer.
8. The preparation method according to claim 4, characterized in that: The wire feeding speed of Cu welding wire is 10-15m / min, and the wire feeding speed of Fe welding wire is 8-12m / min.
9. The preparation method according to claim 4, characterized in that: The welding current of Cu wire is 137~243A, and the welding voltage is 11.6~23.5V. The welding current of Fe wire is 120~226A, and the welding voltage is 11.2~22.3V.
10. Application of the wire-based directed energy deposition laminated structure Cu-Fe additive component according to any one of claims 1 to 3 in high-performance electromechanical devices.
Citation Information
Patent Citations
Amorphous alloy / metal micro-laminated composite and preparation method thereof
CN110756982A
Ti / Al + X composite interlayer for TiAl / nickel-based superalloy connection and diffusion welding method
CN115319261A
Method for regulating and controlling strength and plasticity of high-strength steel through double-wire CMT material increase
CN116984707A
Equipment and method for preparing eutectic high-entropy alloy based on electric arc additive
CN117921135A
Cu-Fe additive part based on double-wire electric arc additive and preparation method of Cu-Fe additive part
CN118543931A